2016
DOI: 10.1179/1743294414y.0000000416
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and microstructural properties of NiCrFeSiBC/Cr3C2 composite coatings – part I

Abstract: NiCrFeSiBC/Cr 3 C 2 composite coatings were developed on to GrA1 boiler steel by high velocity oxy fuel spray process. The aim was to develop the novel composite coating by finding optimum concentration of Cr 3 C 2 in NiCrFeSiBC matrix, which further possesses the superior solid particle erosion resistance. The mechanical and microstructural properties of the developed coatings were critically examined. The as sprayed coatings were characterised by X-ray diffraction, SEM/ energy dispersive spectroscopy analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…The phase composition determined by means of XRD analysis consists, in both cases, of γ-Ni/Ni 3 B solid solution and further phases like CrB and Cr 6 Ni 16 Si 7 . Similar γ-Ni/Ni 3 B phases were already previously reported in the literature [21][22][23]. Corroborating the XRD with the EDX spot analysis, the matrix marked with A in Figure 5a,b consists of the γ-Ni/Ni 3 B phase, the darker region marked with B shows the primary crystals of CrB, while the lighter region of C represents the Cr 6 Ni 16 Si 7 .…”
Section: Sample Roughness and Porosity Calculationsupporting
confidence: 85%
“…The phase composition determined by means of XRD analysis consists, in both cases, of γ-Ni/Ni 3 B solid solution and further phases like CrB and Cr 6 Ni 16 Si 7 . Similar γ-Ni/Ni 3 B phases were already previously reported in the literature [21][22][23]. Corroborating the XRD with the EDX spot analysis, the matrix marked with A in Figure 5a,b consists of the γ-Ni/Ni 3 B phase, the darker region marked with B shows the primary crystals of CrB, while the lighter region of C represents the Cr 6 Ni 16 Si 7 .…”
Section: Sample Roughness and Porosity Calculationsupporting
confidence: 85%
“…It is worth nothing that the use of small nozzles contributes to reduce the porosity by about 4 times (from 12.1% to 2.7%) and increase the hardness from 900 to 1264 HV. Similar porosity (Miguel et al, 2003;Shrestha et al, 2005;Yu et al, 2013;Singh and Kaur, 2016;Wen et al, 2017) and hardness (González et al, 2007a;González et al, 2007b;Singh and Kaur, 2016) values have been reported for thermally sprayed Ni-based coatings. However, the porosity content obtained in the present study for C3 and C4 conditions (2.7% in average), is lower compared to those reported for as-sprayed selffluxing coatings deposited by flame and plasma spraying (Higuera Hidalgo et al, 2001;Kim et al, 2003;Planche et al, 2005;Culliton et al, 2013;Bergant et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…Adhesive/delamination wear mechanism observed for flame remelted supersonic plasma-sprayed NiCrBSi powder with 30% Mo coating under dry sliding wear test [11]. Cr 3 C 2 addition in NiCrBSi powder produced excellent wear resistance coating and bond strength [12,13]. Plasma-sprayed NiCrBSi powder with 4% graphite addition improved the erosion resistance and microhardness [14].…”
Section: Introductionmentioning
confidence: 99%
“…For significant interpretation, the selection of the most suitable test based on the mechanical system and operating condition is essential [22]. Some pieces of the literature have studied the tribological behaviour of nickel and WC-based coating under various test such as dry sliding wear test [23][24][25], abrasive wear test [26], solid particle erosion test [13,27], cavitation erosion test [23,28], and slurry jet liquid impingement test [29].…”
Section: Introductionmentioning
confidence: 99%